Afghan Youth's Expectation for Educational, Economic and Political Development during the Reign of Taliban - Adel, Samiullah; Anoraga, Bhirawa (International Journal of Islamic Studies Higher Education, 2023)
Various aspects of life have been dramatically shifted when the Taliban conquers Afghanistan recently. However, the changes occurring in sectors of education, economy, and politics have been acquired as the prominent issues to be discussed for the three factors will become the ground of the country's development. Thus, the study will be concentrated on the expectation of young Afghani for their country in the three aspects of education, economy, and politics. The study employs the qualitative method of the phenomenological approach. The data is acquired through in-depth interviews with twenty-five informants, consisting of five scholars, seven academicians, and thirteen influential youngsters in Afghanistan. Analysis of the data is conducted through Interactive Miiles and Hubberman technique. The findings indicate four expectations of young Afghanis in general. First, gender equality in education sectors that males and females should gain similar opportunities at every level of education. Second, the duration of primary education should be shortened to twelve years as the reign recently requires elementary education for fourteen years. Third, the current curriculum should be reformed to be a more systematic, professional, and skill-oriented curriculum that graduates are qualified for job demands. Fourth, Despite of high-income tax which almost gains 50%, the reign should lower the income tax to 10% to invite investors to arrive in Afghanistan. Fifth, it is expected that the reign establishes political stability for every community group and the international world. The findings are expected to be relevant input for the reign of the Taliban for a better Afghanistan in the future.